Dielectric parameters measurement with the aid of microwave multimeter - Miroshnyk, A. M.; Zaichenko, O. B.; Rozhnova, T. G. (My University, 2017)
Multiprobe microwave multimeters allow to measure dielectric permittivity of materials along with power, complex reflection coefficient and wavelenght, being universal devices. A method proposed for determining the permittivity of materials on the basis of the mode in the form of an integral equation that is distinguished by the use of the dyadic Green's function as the kernel of the integral equation, with the simplification by variational principles to obtain engineering formulas for calculation measurement uncertainty.
Keywords: dielectric permittivity; complex reflection coefficient; multiprobe microwave multimeter; processing algorithm; measuurement uncertainity